A Coco-nut [sic] Picker, Trinidad - (:unkn) unknown (My University, 2009)
A picture of a man climbing a coconut tree using a rope to assist. A description on the back of the postcard reads "Owing to the height of the palms the gathering of the coco-nuts require specially trained men. They climb with the aid of a rope loop and become so expert that they literally walk up the trunk." Postcard numbered B 8.
Colour: Sepia; Style: Portrait; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Coconut palm--Trinidad and Tobago; Agriculture--Trinidad and Tobago; Blue collar workers--Trinidad and Tobago; Tree climbing--Trinidad and Tobago; Men--Trinidad and Tobago